Cannabinoids for skin diseases and hair regrowth. (7th August 2021) - Gupta, Aditya K.; Talukder, Mesbah
Abstract: The use of cannabis for skin diseases and hair regrowth is at the preliminary stage. Legalization: Many countries have approved cannabis for medical use; however, four countries Canada, Uruguay, South Africa, and Georgia have legalized it for both medical and recreational purposes. The endocannabinoid system: The endocannabinoid system may maintain skin homeostasis; two notable endocannabinoids include 2‐Arachidonoylglycerol (2‐AG) and N ‐arachidonoylethanolamine (AEA). Routes of administration and pharmacokinetics: Topical cannabinoids can avoid the first‐pass metabolism and reduce respiratory side effects; however, the high hydrophobicity of cannabinoids may hinder percutaneous absorption. Skin disorders and hair growth: Human clinical studies suggest that cannabinoids may be used in eczema, acne, pruritus, and systemic sclerosis treatment. Cannabidiol (CBD) may enhance hair growth via multiple mechanisms. Safety: Topical cannabis may cause mild side effects such as pruritus, burning, erythema, and stinging; they are relatively safer than inhalation and oral cannabis. Cannabis use may be associated with allergic symptoms and reduced immune response to live vaccination. Cannabinoids in practice: Despite growing interest, dermatologists should be cautious prescribing cannabinoids due to insufficient clinical data on both efficacy and safety.